Applicability of the Nonverbal Learning Disability Paradigm for Children With 22q11.2 Deletion Syndrome. (March 2014) - Schoch, Kelly; Harrell, Waverly; Hooper, Stephen R.; Ip, Edward H.; Saldana, Santiago; Kwapil, Thomas R.; Shashi, Vandana
Chromosome 22qll.2 deletion syndrome (22qllDS) is the most common microdeletion in humans. Nonverbal learning disability (NLD) has been used to describe the strengths and deficits of children with 22q11DS, but the applicability of the label for this population has seldom been systematically evaluated. The goal of the current study was to address how well the NLD diagnosis characterizes children and adolescents with 22q11DS. A total of 74 children and adolescents with 22q11DS were given neurocognitive, socioemotional, and academic assessments to measure aspects of NLD. Of the cohort, 20% met at least 7 of 9 assessed criteria for NLD; 25% showed verbal skills exceeding their nonverbal skills as assessed by an IQ test; and 24% showed the good rote verbal capacity commonly associated with NLD. Hypothesizing that if the entire cohort did not show consistent NLD characteristics, the descriptor might be more accurate for a distinct subgroup, the authors used latent class analysis to divide participants into three subgroups. However, the lines along which the groups broke out were more related to general functioning level than to NLD criteria. All three groups showed a heightened risk for psychiatric illness, highlighting the importance of careful mental health monitoring for all children with 22qllDS.